Milestones in Green Transition and Climate Compatible Development in Eastern and Southern Africa - Shisanya, Chris A.; Mukuna, Truphena E. (Book collections on Project MUSE., 2015)
It is widely recognised that climate change poses significant serious threats to sustained economic growth and agricultural development, poverty reduction, food security and political stability globally. Nowhere are these challenges more marked than in Africa where two-thirds of all available land is classified either as desert or dry land, in relation to which the Intergovernmental Panel on Climate Change (IPCC) (2013) has classified the continent as the most vulnerable to climate change variability. This anthology is a product of a call from OSSREA to collate evidence based researches in a book in a bid to assess how far countries in eastern and southern Africa are implementing the UNFCCC, Rio+20, Agenda 21 and other global and Africa-wide decisions concerning the need to address climate change. -- Back cover.